2020
DOI: 10.1002/hec.3982
|View full text |Cite
|
Sign up to set email alerts
|

Priority access to health care: Evidence from an exogenous policy shock

Abstract: Access to care is an important issue in public health care systems. Unlike private systems, in which price equilibrates supply and demand, public systems often ration medical services through wait times. Access that is given on a first come, first served basis might not yield an allocation of resources that maximizes the health of a population, potentially creating suboptimal heterogeneity in wait times. In this study, we examine an access disparity between two groups of patients-established patients and new p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Finally, carving out access for new patients by simply not scheduling returning patient visits more than 3 months in advance is associated with a significant reduction in wait times. Yee et al (2020) found that rescinding the Recall Reminder scheduling policy (and allowing returning patients to schedule in advance) effectively increased wait times by 14%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, carving out access for new patients by simply not scheduling returning patient visits more than 3 months in advance is associated with a significant reduction in wait times. Yee et al (2020) found that rescinding the Recall Reminder scheduling policy (and allowing returning patients to schedule in advance) effectively increased wait times by 14%.…”
Section: Discussionmentioning
confidence: 99%
“…Between September 2010 and May 2016, the VHA instituted a nationwide policy called the Recall Reminder policy, which limited access to the schedule for established patients and improved access for new patients. Yee et al (2020) showed that the wait time for new patients seeking primary care appointments was strongly affected by whether established patients had special access to scheduling their follow-up appointments. In many medical centers, established patients tend to crowd out new patients by scheduling their appointments months in advance.…”
Section: Empirical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, SM may enhance access across age groups to improve communication, system navigation, and potentially patient activation reducing the need for in-person visits. However, it may also yield disparate access for new versus established patients 23,24 as in many health systems it is at the first in-person appointment that patients gain access to web portal sign-up information. It is also worth noting that a patient portal account does not imply active portal use.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the above analysis dimensions of the accessibility of healthcare services for the elderly and the construction principles of the index system, this paper establishes an accessibility index system of healthcare services for the elderly that includes potential accessibility, realized accessibility, and sustainable accessibility, according to the existing research results of accessibility of healthcare services for the elderly and the construction practice of local government [ 29 , 30 , 31 ]. The index system includes 3 first level indicators, 12 secondary level indicators, and 23 measurement indicators, as shown in Table 2 .…”
Section: Analysis Framework and Index Systemmentioning
confidence: 99%